CO2 Capture in Ionic Liquids Based on Amino Acid Anions With Protic Side Chains: a Computational Assessment of Kinetically Efficient Reaction Mechanisms - Stefano Onofri; Dr. Henry Adenusi; Dr. Andrea Le Donne; Prof. Enrico Bodo (ChemistryOpen, 2020)
Abstract Absorption and capture of CO2 directly from sources represents one of the major tools to reduce its emission in the troposphere. One of the possibilities is to incorporate CO2 inside a liquid exploiting its propensity to react with amino groups to yield carbamic acid or carbamates. A particular class of ionic liquids, based on amino acids, appear to represent a possible efficient medium for CO2 capture because, at difference with current industrial setups, they have the appeal of a biocompatible and environmentally benign solution. We have investigated, by means of highly accurate computations, the feasibility of the reaction that incorporates CO2 in an amino acid anion with a protic side chain and ultimately transforms it into a carbamate derivative. Through an extensive exploration of the possible reaction mechanisms, we have found that different prototypes of amino acid anions present barrierless reaction mechanisms toward CO2 absorption.